Penguatan Kapasitas Masyarakat Melalui Edukasi Silvofishery Kepiting Bakau (Scylla sp.) di Desa Buruk Bakul Provinsi Riau - Indra Suandy; Budijono Budijono; Ali Asfar; Wan Muhammad Yunus; Endang Purnawati Rahayu; Zulmeliza Rasyid; Novita Rany (CANANG: Jurnal Pengabdian Masyarakat, 2025)
The degradation of mangrove ecosystems and declining populations of mangrove crabs (Scylla sp.) in the coastal areas of Bengkalis necessitate the implementation of sustainable management strategies that integrate ecological and economic aspects. This community service program aims to enhance the capacity of the Sekat Bakau Group in Buruk Bakul Village through education and training in jerry can-based silvofishery systems as an environmentally friendly aquaculture innovation. Activities were conducted from June to December 2024, involving 20 participants through three phases: planning, implementation, and evaluation using a pre-test post-test design. Results demonstrate a significant increase in participants' knowledge from an average of 60.3% (pre-test) to 90.5% (post-test), accompanied by successful technical skill transfer in constructing jerry can-based aquaculture units. The program successfully fostered ecological awareness, practical skills, and community readiness for silvofishery implementation, although field validation is required to measure actual economic and ecological impacts. The participatory educational approach proved effective as an empowerment strategy for coastal communities in realizing sustainable fisheries resource management